(untitled) (Acta Scientiarum. Technology, 2017)
The goal of this work was to study the adsorption equilibrium of ions Zn2+ and Cd2+ using bovine bone char in fixed bed columns. Dynamic tests were performed with upstream flow fixed bed column, at 30oC and average particle diameter of 0.08 mm. Initially, the optimal operating flow rate was determined, which was 4 mL min.-1 for both metals. The dynamic isotherms, obtained by mass balance in the breakthrough curves, were fitted to the Langmuir and Freundlich models. Simulations of the dynamics of ion adsorption provided satisfactory results, wherein the mass transfer coefficient was directly affected by the inflow concentration of ions, within the range of the study. Â